DESIGN AND BUILD A STUDENT ATTENDANCE APPLICATION AT MADRASAH ALIYAH POMPANUA BONE DISTRICT BASED ON ANDROID - Vitalocca, Dyah; Yahya, Muhammad; Syafar, Syafar (Fakultas Teknik Universitas Negeri Makassar, 2024)
This research aims to determine the results of the design and effectiveness of the application as well as determine the responses of users of the Android-based student attendance application at Madrasah Aliyah Pompanua, Bone Regency. This research uses an R&D (Research and Development) type of research that uses the waterfall development model. The data collection techniques used were observation, interviews and questionnaires. This application testing uses the ISO/IEC 25010 quality standard which covers 4 aspects including functional suitability, performance efficiency, usability and protability. The application testing results used ISO/IEC 25010 quality, namely the functional suitability aspect testing was carried out by two system experts, and it was found that this application was in the very good category to use. Performance efficiency aspect testing was carried out using the Android Studio profiler by measuring real-time data for CPU, memory and network when the application was used, and the test results obtained good values. Usability aspect testing was carried out by teachers at Madrasah Aliyah Pompanua Bone Regency using a questionnaire and it was found that this application was in the very good category. Protability aspect testing is carried out by running the application using an Android device in various Android versions. Based on these data, it can be concluded that the Android-based student attendance application at Madrasah Aliyah Pompanua, Bone Regency is acceptable for use as a medium that makes it easier for teachers to take attendance and recap student absences at Madrasah Aliyah Pompanua, Bone Regency